Queen Maria’s last will (Confluenţe Bibliologice, 2026)
This article examines „Regina Maria, ultima dorință/ The Final Wishe of Queen Maria” by Tatiana Niculescu Bran, which analyzes and publishes Queen Maria’s testament, a document of deep historical significance. It explores the circumstances in which the author uncovered the queen’s spiritual world and the symbolic repatriation of her heart in 2015 to Peleșor Castle with military honors. Key excerpts from the 1933 Balcic testament reveal her love for Romania, gratitude to her people, and attachment to cherished places, portraying Queen Maria as a symbol of devotion, courage, and national spirit.
Keywords: Marie of Romania (1875-1938); Romanian history